2010
DOI: 10.4300/jgme-d-09-00048.1
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Residents' Behavior and the Thomas-Kilmann Conflict MODE Instrument

Abstract: Objective To assess if the Thomas-Kilmann Conflict MODE Instrument predicts residents’ performance. Study Design Nineteen residents were assessed on the Thomas-Kilmann conflict modes of competing, collaborating, compromising, accommodating, and avoiding. Residents were classified as contributors (n  =  6) if they had administrative duties or as concerning (n  =  6) if they were on remediation for academic performance and/or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
14
0
3
Order By: Relevance
“…127,128 Another training program reported positive results in training residents 129 and attributed the program's success to a longitudinal and skill-based structure that supported the residents in their leadership paths to advocate for children's health. Another small study showed that the Thomas-Kilmann Conflict Mode Instrument predicted Accreditation Council for Graduate Medical Education (ACGME) evaluations of residents, 129 suggesting the relevance of EI evaluation to ACGME competencies. In contrast, other studies have not shown a benefit from incorporating EI training into graduate medical education training.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…127,128 Another training program reported positive results in training residents 129 and attributed the program's success to a longitudinal and skill-based structure that supported the residents in their leadership paths to advocate for children's health. Another small study showed that the Thomas-Kilmann Conflict Mode Instrument predicted Accreditation Council for Graduate Medical Education (ACGME) evaluations of residents, 129 suggesting the relevance of EI evaluation to ACGME competencies. In contrast, other studies have not shown a benefit from incorporating EI training into graduate medical education training.…”
Section: Ei Is Desired and Relevant Throughout Medical Education And mentioning
confidence: 99%
“…This is in support of our previous observation that residents who successfully execute administrative duties are likely to have a TKI profile that is high in collaborating and competing but low in avoiding and accommodating, and residents who have problems adjusting are likely to have the opposite profile. 12 Faculty evaluation using ACGME competencies and CREOG in-service scores did not correlate with compliance scores, suggesting that these tools measure different parameters. Our findings support the ACGME mandate that assessments by multiple observers using multiple tools at multiple time points are needed to provide a holistic assessment of residents in the 6 competencies.…”
Section: Discussionmentioning
confidence: 94%
“…For administratively successful residents, a Collaborative or Competing mode may be more productive. 6 One possible concern was that a few program directors preferred the Avoiding or Accommodating modes. These 2 modes are clearly appropriate in specific contexts but may not be helpful if used predominantly to handle conflict.…”
Section: Discussionmentioning
confidence: 99%
“…instrument also has been used to differentiate among residents who have problems adjusting versus those who succeed in an administrative role during residency. 6 The Hersey-Blanchard Situational Leadership (HBSL) model, developed in the late 1960s, focuses on leaders' assessment of their followers' needs and their adoption of the most appropriate leadership style. 7 Followers may have variable degrees of competence and/or commitment (eg, a group of new interns may have little knowledge of systemsbased practice tools and little motivation to learn them).…”
Section: And Thementioning
confidence: 99%